On Sandwich Theorems Results for Certain Univalent Functions Defined by Generalized Operators - Atshan, Waggas Galib; Ali, Aqeel Ahmed Redha (Iraqi Journal of Science, 2021)
In this present paper, we obtain some differential subordination and superordination results, by using generalized operators for certain subclass of analytic functions in the open unit disk. Also, we derive some sandwich results.